COPZ1: an example of non-oncogene addiction in human tumors - Di Marco, Tiziana; Vergaro, Debora; Greco, Angela (Frontiers in Pharmacology, 2025)
Non-oncogene addiction (NOA) indicates that tumor cell growth/survival requires the activity of genes/pathways not oncogenic per sé, and dispensable for normal cells. NOA genes provide a wide repertoire of novel therapeutic exploitable tumor vulnerabilities. A large body of evidence demonstrates the dependency of several tumors such as breast, prostate, ovary, thyroid, glioblastoma and LUAD, on the activity of COPZ1, a component of the heptameric COPI complex. Thus, COPZ1 is emerging as a potential novel therapeutic target for tumors of different origin. In different tumor models COPZ1 inhibition was found implicated in abortive autophagy, ER stress and activation of ferroptosis. In this review we summarize the different studies characterizing COPZ1 as a NOA gene in different tumor types, and discuss potential issues related to its targeting.